THE DEVELOPING OF THE CONSTANT OF PROBABILITY EQUATION OF CRESCENT. - MAJEED M. JARAD; THAAIR M. SLEEBY (مجلة جامعة الانبار للعلوم الصرفة, 2013)
The aim of this study is to improve the value of the Constant of probability Equation for sighting the crescent. The factors {age of the moon, moon altitude, anomaly of the sun, the duration of stay Crescent (mukth)} for many years has been calculated and used to improve the constant of the equation of the probability of sighting the crescent. The relation between these factors were found to be Linear. We found through the analysis of these factors that the best value of the constant is ( 0.95 ) and these value give a very good results of the probability of seeing the new moon with naked eye. The results were more accurate and in a good agreement with other criteria